On a model for the growth of an invasive avascular tumor - Avila, J. A J; Lozada-Cruz, G. [UNESP] (Natural Sciences Publishing, 2013)
This paper is devoted to study the 1D model of invasive avascular tumor growth, which takes into account cell division, death, and motility, proposed by Kolobov and collaborators in 2009. First, we examine the existence and uniqueness of the solution to this model. Second, we studied qualitatively and numerically the traveling wave solutions. Finally, we show some numerical simulations for the cell density and nutrient concentration. © 2013 NSP Natural Sciences Publishing Cor.
Keywords: Existence of solution; Invasive avascular tumor; Numerical simulation.; Traveling wave